Clinical features and survival of patients with indolent systemic mastocytosis defined by the updated WHO classification. Issue 8 (16th March 2020) - Trizuljak, Jakub; Sperr, Wolfgang R.; Nekvindová, Lucie; Elberink, Hanneke O.; Gleixner, Karoline V.; Gorska, Aleksandra; Lange, Magdalena; Hartmann, Karin; Illerhaus, Anja; Bonifacio, Massimiliano; Perkins, Cecelia; Elena, Chiara; et al.
Abstract: Background: In indolent systemic mastocytosis (ISM), several risk factors of disease progression have been identified. Previous studies, performed with limited patient numbers, have also shown that the clinical course in ISM is stable and comparable to that of cutaneous mastocytosis (CM). The aim of this project was to compare the prognosis of patients with ISM with that of patients with CM. Methods: We employed a dataset of 1993 patients from the registry of the European Competence Network on Mastocytosis (ECNM) to compare outcomes of ISM and CM. Results: We found that overall survival (OS) is worse in ISM compared to CM. Moreover, in patients with typical ISM, bone marrow mastocytosis (BMM), and smoldering SM (SSM), 4.1% of disease progressions have been observed (4.9% of progressions in typical ISM group, 1.7% in BMM, and 9.4% in SSM). Progressions to advanced SM were observed in 2.9% of these patients. In contrast, six patients with CM (1.7%) converted to ISM and no definitive progression to advanced SM was found. No significant differences in OS and event‐free survival (EFS) were found when comparing ISM, BMM, and SSM. Higher risk of both progression and death was significantly associated with male gender, worse performance status, and organomegaly. Conclusion: Our data confirm the clinical impact of the WHO classification that separates ISM from CM and from other SM variants. Abstract : Division of mastocytoses according to updated WHO Classification is clinically relevant. Overall survival is worse in indolent systemic mastocytosis compared to cutaneous mastocytosis. Trephine biopsy is necessary to distinguish indolent systemic mastocytosis from cutaneous mastocytosis.